Potential of Hyacinth Activated in Lowering Levels of Lead Heavy Metals by Method of Atomic Absorption Spectrophotometry - Wardani, Dita Kusuma; Alawiyah, Tuti; Tambun, Madschen Sia Mei Ol Siska Selvija (Lamintang Education and Training Centre, in collaboration with the International Association of Educators, Scientists, Technologists, and Engineers (IA-ESTE), 2021)
The Barito River as the largest and longest river in South Kalimantan has been convicted as the most polluted river on an international level. Where one of the most commonly found compounds is the heavy metal lead (Pb) with a high enough levels that alternatives are needed to reduce the levels of the metal. One way to reduce the levels of such heavy metals is to use activated carbon hyacinth. So the activated carbon from hyacinth is made in accordance with SII No.0258-79 and knows the effect of variations in the administration of activated carbon hyacinth at a time of 15 minutes, 30 minutes and 45 minutes in lowering the levels of lead heavy metals (Pb). The research method used to determine the effect of variations in the administration of activated carbon hyacinth is by quantitative testing using the Atomic Absorption Spectrophotometry tool. The results showed that activated carbon hyacinth has met SII No.0258-79 with a randemen test result of 15%, water content of 3%, and absorption of iodine of 241.16 mg / gram. Significant value produced 0.742 with regression value (r) 0.999 and resulted in decreased lead metal levels in the variation of 15 minutes activated carbon administration of -0.030 mg / l with an absorption of 120%, 30 minutes of 0.073 mg / l with an absorption of 48% and 45 minutes of -0.097 mg / l with an absorption of 167%. Hyacinth activated carbon can be used to lower the levels of lead heavy metals (Pb) with a maximum contact time of 45 minutes by 167%.